Temperature Impact on Tweed Structure Formation on Aluminum Single-Crystal Foil Surface under Cyclic Tension; AIP Conference Proceedings; Vol. 2051 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2018 (AMHS’18) - Kuznetsov P. V. Pavel Viktorovich (2018, 2018)
Title screen